BENTUK RESOLUSI KONFLIK DALAM PILKADA: Kasus Pilkada Kota Yogyakarta dan Kabupaten Jepara - IKHSAN DARMAWAN, IKHSAN DARMAWAN (Politika: Jurnal Ilmu Politik, 2010)
AbstractOne of concerns under the implementation of direct local election is the raising of conflictintensity. There are conflicts in the local election in Yogyakarta Municipality and Jepara Region. Theconflicts are about: (1) Whether the local election held or not especially because there is situation thatthere is only a couple of candidate registered, and (2) if the local election held, when will it be held.This thesis tries to answers two questions: (1) How the conflict resolution in Yogyakarta Municipalityand Jepara Region’s local election held?, (2) What is the form of conflict resolution used inYogyakarta Municipality and Jepara Region’s local election?The result of this research is that method of conflict resolutions that used in Yogyakarta’s municipality’local election are conciliation and arbitration. On the other side, the method of conflict resolutions thatused in Jepara Region’s local election are conciliation, mediation, and arbitration.Keywords: Conflict resolution, Local Election